2020
DOI: 10.1007/s10658-020-02156-w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of apple blotch resistance in wild apple germplasm (Malus spp.) accessions

Abstract: Diplocarpon coronariae causes apple blotch, which results in significant economic losses. Resistance to apple blotch in commercial apple cultivars has not been reported in recent literature. The Malus germplasm collection from the Fruit Genebank of the Julius Kühn-Institut that is maintained in Dresden, Germany consists of 516 accessions of about 49 Malus species. This apple gene pool was evaluated for resistance to Diplocarpon coronariae. A four-year field survey was subsequently followed by artificial inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Each Petri dish was moistened with 10 mL of tap water. The extraction of the inoculum and the inoculation was performed according to a method of Wöhner et al [29,30] with modifications reported in Richter et al [25].…”
Section: Plant Materials and Diplocarpon Coronariae-resistant Leaf Testmentioning
confidence: 99%
“…Each Petri dish was moistened with 10 mL of tap water. The extraction of the inoculum and the inoculation was performed according to a method of Wöhner et al [29,30] with modifications reported in Richter et al [25].…”
Section: Plant Materials and Diplocarpon Coronariae-resistant Leaf Testmentioning
confidence: 99%